SISTEM INFORMASI PENGAJUAN KREDIT BERBASIS WEB MENGGUNAKAN AGILE DEVELOPMENT METHODS PADA BANK BRI UNIT KOLONEL SUGIONO - Irfan Mahendra; Deny Tresno Eby Yanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2018)
This research is intended to design web-based credit application information system using agile development methods at Bank BRI Unit Kolonel Sugiono. Currently in general the credit application process is still done manually, from the process of delivering information about credit to customers, the process of submitting credit applications, and processing data and credit files. This is considered to cause the credit application process to be ineffective and a long time. Based on these problems, then the development of a web-based credit application information system using agile development methods, which is expected to produce a quality information system in a short time. The conclusion of this study is to use agile development methods, information system development carried out can produce quality information systems and fit with software requirement in a short time.